A first phylogenomic hypothesis for Eulophidae (Hymenoptera, Chalcidoidea). Issue 9 (18th March 2020) - Rasplus, Jean-Yves; Blaimer, Bonnie B.; Brady, Seán G.; Burks, Roger A.; Delvare, Gérard; Fisher, Nicole; Gates, Michael; Gauthier, Nathalie; Gumovsky, Alex V.; Hansson, Christer; Heraty, John M.; Fusu, Lucian; et al.
ABSTRACT: Eulophidae is a hyper-diverse family of chalcidoid wasps with 324 genera, about 5300 described species and probably thousands of others to be described. Until now, the absence of unequivocal morphological apomorphies and the low resolution provided by the handful of Sanger sequenced genes have hampered the reconstruction of phylogenetic relationships within the family. Here, we used ultra-conserved elements and their flanking regions to resolve relationships among 84 species of eulophids included in 63 genera representing all subfamilies and most tribes, plus 15 outgroups. Our analyses recover all traditional Eulophidae subfamilies and tribes with high support and globally agree with the traditional classification of the family. Our results confirm that Eulophinae + Tetrastichinae is the sister group of (Opheliminae + Entiinae) + Entedoninae. At the generic level, our analyses provide high support for intergeneric relationships for which morphology and Sanger markers previously failed to provide resolution. Our results also confirm that Trisecodes does not group with Eulophidae and may not belong to this family; however, its correct classification still awaits a large-scale phylogenomic hypothesis for Chalcidoidea. This work opens new avenues towards a better understanding of the evolutionary history, biogeography and evolution of host–parasitoid associations in this hyper-diverse family of chalcidoid wasps.